All of Us with Wings - Keil, Michelle Ruiz (New York, NY : Soho Teen, 2019)
Seventeen-year-old Xochis life changed when she became governess to precocious twelve-year-old Pallas, but the duo unintentionally summons a pair of ancient creatures determined to right the wrongs of Xochis adolescence.
Keywords: Governesses -- Fiction; Revenge -- Fiction; Musicians -- Fiction; Runaway teenagers -- Fiction; Mexican Americans -- Fiction; San Francisco (Calif.) -- Fiction